A C-type lectin (CL11X1-like) from Nile tilapia (Oreochromis niloticus) is involved in host defense against bacterial infection. (July 2018) - Mu, Liangliang; Yin, Xiaoxue; Xiao, Yanhui; Bian, Xia; Yang, Yanjian; Wu, Liting; Ye, Jianmin
Abstract: Collectins, a subfamily of the C-type lectins, are able to bind non-self glycoconjugates on the surface of microorganisms and inhibit infection by direct neutralization, agglutination and/or opsonization, which play important roles in innate immunity. In this study, a CL11X1-like collectin (OnCL11X1) was identified from Nile tilapia ( Oreochromis niloticus ) and characterized at expression and agglutination functional levels. The open reading frame of OnCL11X1 is 840 bp of nucleotide sequence encoding polypeptides of 279 amino acids. The deduced amino acid sequence is highly homology to teleost and similar to mammalian CL11X1, containing a canonical collagen-like region, a carbohydrate recognition domain and a neck region. Expression analysis revealed that the OnCL11X1 was highly expressed in the liver, and widely exhibited in other tissues including kidney, intestines and spleen. In addition, the OnCL11X1 expression was significantly up-regulated in spleen and anterior kidney following challenges with a Gram-positive bacterial pathogen ( Streptococcus agalactiae ) and a Gram-negative bacterial pathogen ( Aeromonas hydrophila ). The up-regulation of OnCL11X1 expression was also demonstrated in hepatocytes and macrophages in vitro stimulation with S. agalactiae and A. hydrophila . Recombinant OnCL11X1 protein was able to agglutinate both S. agalactiae and A. hydrophila in vitro and promote the phagocytosis by macrophages. Taken together, the results of this study indicated that OnCL11X1, possessing apparent agglutination and opsonization ability to bacterial pathogens, might be involved in host defense against bacterial infection in Nile tilapia. Highlights: The X1 ( CL11X1 gene was identified in Nile tilapia) OnCL11 . OnCL11X1 was significantly up-regulated following challenges with Streptococcus galactiae and Aeromonas hydrophila . Recombinant OnCL11X1 possessed agglutination and opsonization ability to Streptococcus galactiae and Aeromonas hydrophila .